Perancangan Video Musik “Menit Tambahan” oleh Band Lomba Sihir Berbasis Animasi - Farrellino Jason Lie; Andreana Lingga Sekarsari (Penerbit dan Percetakan, CV. Picmotiv, 2025)
The visual profile of a band is a way of communication that supports their listeners’ listening experience. This study aims to make an animated music video for “Menit Tambahan” by Lomba Sihir to expand the song’s idea through the animated music video visuals and as a promotional tool. This study uses the qualitative method through observing animation videos and animated music videos, also through interviews with the creative director for the song “Menit Tambahan” and a director of an animated music video. The result shows that the music video for “Menit Tambahan” by Lomba Sihir can be an example of visual exploration based on animation that enriches artistic values and promotion from a body of work. Visual approach employed takes into account illustration style, color selection, movement rhythm, and synchronization between animation and music in order to create a strong unity of message. Through this design, the animated music video is expected not only to function as an aesthetic complement, but also as a visual communication medium capable of expanding audience reach, strengthening the band’s visual identity, and enhancing the appeal and interpretation of the song “Menit Tambahan”